Sexing the Self / Gendered Positions in Cultural Studies - Probyn Elspeth (Rouledge, 1993)
An important and highly original contribution to the problem of experience in feminism and cultural studies. Acknowledgements, Introduction: Speaking the Self and Other Feminist Subjects, A Problematic: Speaking the Self, Problematic Selves: The Irony of the Feminine, Moving Selves and Stationary Others: Ethnography's Ontological Dilemma, Materializing Locations: Images and Selves, Technologizing the Self: Foucault and ''Le Souci du Toi'', Without her I'm Nothing: Feminisms with Attitude, Conclusion: Sexing the Self, Bibliography, Index.